COMBINING ABILITY EFFECTS AND PER-SE PERFORMANCES OF MORPHO REPRODUCTIVE TRAITS IN RICE (Oryza sativa L.) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
To study combining ability effects of developed CMS and restorer lines an experiment was carried out at the experimental farm, Department of Genetics and Plant Breeding, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during Aman 2011 and Boro 2011-12 following RCBD design through line × tester analysis in three replications. Five known CMS lines and sixteen developed Restorer lines were considered for through line × tester analysis. Among sixteen restorer lines, only four showed significant negative GCA effects for all these three traits for earliness. The estimated of gca effects of parents indicated that seven parents and sixteen crosses contributed highly significant negative effects for plant height which were responsible for dwarfing character. Fifteen crosses and eight parents showed significant negative sca estimates for days to first flowering and twenty crosses for maturity. Considering both SCA effects and per se performances for days to 1st flowering and maturity; the crosses of IR 58025A with RG-BU08-005R, RG-BU08-006R, RG-BU08-016R, RG-BU08-018R and RG-BU08-025R were found as the best specific combiner. Among 80 crosses fifty two crosses showed significant positive SCA effects along with above average perse performances for grain yield. Ten crosses of IR 58025A, seven crosses of GAN46A, fourteen crosses of IR 62829A, nine crosses of IR 68888A and ten crosses of BRRI 1A showed significant positive SCA effects along with mean values resulting significant positive SCA effects and above average perse performances with all five CMS lines for grain yield.